Carbon fiber precursor and preparation method and application thereof

By controlling the crystallinity, grain size and orientation of polyacrylonitrile carbon fiber primitives and optimizing the steam drafting process, the problems of many wool and low performance of carbon fibers during pre-oxidation are solved, and high strength, high mold and high toughness carbon fiber primitives are achieved.

CN116024680BActive Publication Date: 2025-03-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111248993.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-26
Publication Date
2025-03-25
Estimated Expiration
2041-10-26

AI Technical Summary

Technical Problem

In the prior art, there are many wool filaments during the pre-oxidation process and the strength, modulus and elongation of the carbon fiber are relatively low.

Method used

A method of manufacturing polyacrylonitrile carbon fiber raw silk is adopted to reduce the generation of wool during pre-oxidation by controlling the fiber crystallinity, grain size and orientation before and after steam drafting, and optimize the steam drafting process conditions to improve the mechanical properties of carbon fibers.

Benefits of technology

It effectively reduces the generation of wool filaments during pre-oxidation, improves the strength, modulus and elongation of carbon fibers, and obtains high-strength, high-model, and high-tough carbon fiber filaments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003321799710000051
    Figure BDA0003321799710000051
  • Figure BDA0003321799710000052
    Figure BDA0003321799710000052
  • Figure BDA0003321799710000053
    Figure BDA0003321799710000053
Patent Text Reader

Abstract

A carbon fiber precursor and its preparation method and application. The present invention relates to a method for preparing polyacrylonitrile carbon fiber precursor, which mainly solves the problems of many hairy fibers in the pre-oxidation process and low carbon fiber strength, modulus and elongation in the prior art. The present invention adopts a method for manufacturing polyacrylonitrile carbon fiber precursor, adopts dry-jet wet spinning, and includes a steam drawing step, wherein the crystallinity of the fiber before steam drawing is 60-75%, and the orientation is 0.65-0.9, and under a steam pressure of 0.2-0.7MPa, the residence time of the drawing section is 2-6s, the drawing multiple is 2-5 times, the crystallinity of the fiber is increased to 68-90%, and the orientation is increased to 0.9-0.99. The technical solution solves the problem well and can be used in the industrial production of polyacrylonitrile carbon fiber precursor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon fiber, and in particular relates to a carbon fiber precursor and a preparation method and application thereof. Background Art

[0002] Carbon fiber has many excellent properties and is used most in the industrial field, with its use in the field of sports goods increasing year by year. The carbon fiber industry plays a very important role in the upgrading of pillar industries in developed countries and even in improving the overall quality of the national economy. It is also of great significance to the adjustment of my country's industrial structure and the replacement of traditional materials.

[0003] High-performance carbon fiber is an important core basic material. Western countries regard it as a key material, impose strict technology and equipment embargoes on China, and use various means to suppress the research and development progress of domestic carbon fiber. As research and development, production and application units and all practitioners in the field of carbon fiber, we have the obligation and responsibility to promote the progress of domestic carbon fiber to a higher level. In the face of severe international situations, it is necessary to overcome the key core technical barriers in the field of carbon fiber, prepare high-performance and high-quality carbon fiber, achieve a big explosion in both production and demand, break the current pattern of carbon fiber supply chain worldwide, become an important part of the international carbon fiber industry, and lay a solid material foundation for the development of my country's national economy and the progress of advanced industries.

[0004] High-quality carbon fiber precursors must have the characteristics of few surface defects, few pore structures, dense structure, good tensile properties and high heat resistance. There are many precursors that can be used to prepare carbon fiber. Currently, more than 90% of carbon fibers on the market are made from PAN precursors. PAN-based carbon fibers have the characteristics of high carbon yield, excellent mechanical properties and mature technology, and have become the main products of carbon fiber. The use of dimethyl sulfoxide as a solvent to prepare polyacrylonitrile-based carbon fiber precursors has the characteristics of low toxicity and high solubility of polyacrylonitrile copolymers in solvents. It is also an important solvent system for preparing high-strength, high-modulus and high-toughness polyacrylonitrile carbon fiber precursors. Compared with wet spinning, dry-jet wet spinning has a faster spinning speed and can spin high molecular weight and high solid content solutions. It is the main process for preparing high-strength, high-modulus and high-toughness polyacrylonitrile carbon fibers.

[0005] The modulus and strength of carbon fiber are closely related to the preferred orientation of graphite crystals along the fiber axis and the pore structure in the fiber. The changes and formation of these structures are closely related to the acquisition of spinning solution, the preparation of precursors, and the subsequent pre-oxidation and carbonization processes. The structure and defects of the precursors will be inherited into the carbon fiber during the pre-oxidation and carbonization process, causing irreversible effects on the structure and performance of the carbon fiber.

[0006] Steam drawing is an important step in the process of preparing polyacrylonitrile-based carbon fiber precursor by dry-jet wet spinning. Patents JP5012089B2, JPWO2018168685A1, JP4983641B2, JP2008214795A, and CN111088543A disclose a method for preparing polyacrylonitrile-based carbon fiber precursor by dry-jet wet spinning. The patents only disclose the tension and mechanical properties of steam-drawn fibers and pre-oxidized fibers, but do not disclose the process, structure, and performance relationship of high-characteristic viscosity fibers suitable for steam drawing. In the dry-jet wet spinning steam drawing process, there are many factors that affect the steam drawing process. The steam pressure and temperature in the steam drawing chamber, the drawing multiple, and the residence time of the fiber in the drawing chamber will affect the structure and properties of the carbon fiber precursor, and thus affect the quality of the pre-oxidized fibers and the final carbon fiber. Moreover, during the high-pressure steam drawing stage, any change in process conditions will lead to unstable tension in the drawing process, which will cause more defects in the structure of the carbon fiber precursor. The friction between the filaments will cause the pre-oxidized yarn to more easily produce more hairy fibers, which will ultimately lead to the deterioration of the strength, modulus and elongation of the obtained carbon fiber. Summary of the invention

[0007] The main technical problem solved by the present invention is the problem of many hairs in the pre-oxidation process and low strength, modulus and elongation of carbon fiber in the prior art. The present invention solves the above technical problems by adopting a method for manufacturing polyacrylonitrile carbon fiber precursor, and has the advantages of less hairs in the pre-oxidation process and good strength, modulus and elongation of carbon fiber.

[0008] One of the purposes of the present invention is to provide a method for preparing carbon fiber precursor, comprising the step of steam drawing, wherein the crystallinity of the fiber before steam drawing is 60-75%, the orientation degree is 0.65-0.9, and the crystallinity of the fiber after steam drawing with a steam pressure of 0.2-0.7 MPa, a drawing residence time of 2-6 s, and a drawing ratio of 2-5 times is 68-90%, and the orientation degree is 0.9-0.99; preferably, the crystallinity of the fiber before steam drawing is 65-75%, the orientation degree is 0.75-0.90, and the crystallinity of the fiber after steam drawing with a steam pressure of 0.3-0.6 MPa, a drawing residence time of 4-5 s, and a drawing ratio of 2-2.5 times is 75-85%, and the orientation degree is 0.93-0.99.

[0009] Preferably, the grain size of the fiber before steam drawing is 6 to 8 nm, and the grain size of the fiber after steam drawing is 8 to 10.5 nm; preferably, the grain size of the fiber before steam drawing is 6.5 to 7.5 nm, and the grain size of the fiber after steam drawing is 9 to 10.5 nm;

[0010] The strength of the steam-drawn fiber is 7-15 cN / dtex, the modulus is 150-235 cN / tex, and the elongation is 7-12%. Preferably, the strength of the steam-drawn fiber is 8.5-13 cN / dtex, the modulus is 170-225 cN / tex, and the elongation is 8.5-12%;

[0011] The fiber fineness after steam drawing is 0.55-1.10 dtex, and preferably, the fiber fineness after steam drawing is 0.60-0.92 dtex.

[0012] The preparation method specifically comprises the steps of extruding polyacrylonitrile stock solution by dry-jet wet spinning, and then stretching by air segment, solidifying, washing, hot water drawing, oiling, drying and densification, steam drawing, and steam heat setting to obtain the carbon fiber precursor.

[0013] Specifically,

[0014] In the above preparation method, the intrinsic viscosity of the polyacrylonitrile stock solution is 3.0 to 5.5 dL / g, preferably 3.5 to 4.8 dL / g.

[0015] In the above preparation method, the length of the air segment is 1 to 15 mm, preferably 5 to 10 mm.

[0016] In the above preparation method, the draft ratio of the solidification molding is 1-5, preferably 1-3.

[0017] In the above preparation method, the hot water stretching is at least level 4, wherein the hot water stretching temperature is 90-100°C, the total stretching ratio is greater than or equal to 4 times, and the fourth hot water stretching ratio is greater than 1.5 times; preferably, the hot water stretching temperature is 95-99°C, the total stretching ratio is 4.5-6.0 times, and the fourth hot water stretching ratio is 1.6-3.0 times.

[0018] In the above preparation method, the drying and densification temperature is 90-160°C, and no stretching is applied; preferably, the drying and densification temperature is 100-140°C.

[0019] The second object of the present invention is to provide a polyacrylonitrile carbon fiber precursor prepared by the above preparation method.

[0020] The third object of the present invention is to provide a high-strength, high-modulus and high-tenacity carbon fiber prepared from the above-mentioned polyacrylonitrile carbon fiber precursor.

[0021] In the above technical scheme, the polyacrylonitrile-based precursor is not particularly limited in other aspects and can be prepared from the polyacrylonitrile spinning solution commonly used in the art by the spinning process commonly used in the art. The polyacrylonitrile spinning solution and the spinning process are not particularly limited. The polyacrylonitrile copolymer used in the present application can be prepared from the comonomer commonly used in the art. For example, but not limited to, the polyacrylonitrile comonomer is a vinyl-containing monomer, and the comonomer is preferably one or more of acrylates, vinyl esters, acrylamides, sulfonates, and ammonium salts.

[0022] During the preparation of the precursor, steam drawing has a significant effect on the polyacrylonitrile carbon fiber precursor in the process of preparing high-strength, high-modulus and high-tenacity carbon fibers, which can effectively reduce the generation of hairy fibers during the pre-oxidation process and the prepared carbon fibers have the characteristics of high strength, high modulus and high tenacity. The present invention firstly controls the crystallinity, grain size and orientation of high characteristic viscosity fibers during steam drawing at a relatively low steam pressure to avoid the generation of more hairy fibers during the pre-oxidation process due to the small proportion of ordered fiber structures. Secondly, the present invention controls the numerous influencing factors (steam pressure and temperature, drawing multiple and residence time) during the steam drawing process of the fiber to avoid the deterioration of carbon fiber strength, modulus and elongation due to any significant changes in process conditions.

[0023] By adopting the technical solution of the present invention, the number of fiber hairs is found to be at least 21 every 5 hours during the pre-oxidation process through online camera statistics. The tensile strength of the prepared carbon fiber can reach 5.7 GPa, the modulus can reach 379 GPa, and the elongation can reach 1.5%, achieving good technical effects. DETAILED DESCRIPTION

[0024] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0025] The test instruments and test conditions used in the examples are as follows:

[0026] The crystallinity and orientation of the fiber during steam drawing were tested by X-ray diffraction to obtain experimental data. After deducting the air background, PeakFit was used for peak separation. The crystallinity of the fiber was calculated according to formula (1), the grain size was calculated according to Scherrer formula (2), and the orientation of the crystal area was calculated by the half-width of the azimuthal scanning curve and according to formula (3).

[0027]

[0028]

[0029]

[0030] The linear density of the fiber is obtained by cutting the 30 cm tow in front of the last drawing roller after the steam drawing cavity online through the fixed length device, and then placing the fiber and the fixed length device in an oven for drying to avoid changes in the fiber length due to the drying process. Finally, the linear density of the fiber is obtained by dividing the weight of the dried fiber (in g) by the total length of the fiber (in 10,000 meters). Each measurement is made 10 times and the average value is taken.

[0031] The mechanical properties of carbon fiber precursor are measured using GB / T 14337-2008.

[0032] The mechanical properties of carbon fiber are measured using GB / T 3362~2017.

[0033] The hairy fibers of the yarn bundle during the pre-oxidation process were obtained by counting the number of hairy fibers for 5 hours using an online camera.

[0034] [Example 1]

[0035] 1. The preparation of the precursor for polyacrylonitrile carbon fiber of the present invention adopts a dry-jet wet spinning method. The intrinsic viscosity of the spinning solution used is 3.5 dL / g and the solid content is 18%. The spinning solution is accurately measured and filtered by a metering pump, and then extruded through a spinneret with 4000 holes and a pore size of 100 μm. After a 5 mm air section, it enters a coagulation bath of a dimethyl sulfoxide aqueous solution for coagulation, with a concentration of 30% and a coagulation draft ratio of 1.5. After that, it is washed with water and stretched with four levels of hot water at temperatures of 95°C, 96°C, 97°C, and 99°C, respectively, and the draft ratios are 1.35, 1.40, 1.50, and 1.60, respectively; after oiling, it is subjected to a two-stage drying and densification treatment, The temperatures are 115°C and 125°C respectively, the crystallinity of the fiber is 65%, the grain size is 6.6nm, and the orientation degree is 0.77; during the steam drawing process, the spinning speed is 25m / min, the steam pressure is 0.3MPa, the residence time in the drawing section is 5s, and the drawing ratio is 2.5 times. After steam drawing, the crystallinity of the fiber is 75%, the grain size is 9.5nm, and the orientation degree is increased to 0.93; finally, after heat setting and winding, high-strength, high-modulus, and high-toughness polyacrylonitrile carbon fiber precursor is obtained, the linear density of the precursor is 0.90dtex, the strength and modulus are 8.5cN / dtex and 171cN / dtex respectively, and the elongation is 10.5%.

[0036] 2. In the preparation of the polyacrylonitrile carbon fiber of the present invention, the raw silk obtained in step 1 is pre-oxidized at 180-260°C, and the total pre-oxidation draft ratio is 0.95 to obtain pre-oxidized fiber; then low-temperature carbonization and high-temperature carbonization are carried out at 300-750°C and 800-1500°C, and the draft ratio is 0.96 times; thereafter, graphitization treatment is carried out at 2800°C, and finally, surface treatment, water washing, sizing, 120°C drying and wire collection are carried out to obtain high-strength, high-modulus and high-tenacity carbon fiber.

[0037] The last roller in the pre-oxidation process was counted by an online camera. The number of hairy fibers in the fiber at the last outlet was 21 every 5 hours. The carbon fiber had a tensile strength of 5.6 GPa, a modulus of 367 GPa, and an elongation of 1.6%.

[0038] [Example 2]

[0039] 1. The preparation of the precursor for polyacrylonitrile carbon fiber of the present invention adopts a dry-jet wet spinning method. The intrinsic viscosity of the spinning solution used is 4.6 dL / g and the solid content is 18%. The spinning solution is accurately measured and filtered by a metering pump, and then extruded through a spinneret with 4000 holes and a pore size of 100 μm. After a 7 mm air section, it enters a coagulation bath of a dimethyl sulfoxide aqueous solution for coagulation, with a concentration of 30% and a coagulation draft ratio of 3. After that, it is washed with water and stretched in four stages with hot water at temperatures of 97°C, 98°C, 98°C, and 99°C, respectively, and the draft ratios are 1.5, 1.7, 2.1, and 2.5, respectively; after oiling, it is subjected to a two-stage drying and densification treatment at temperatures of 1.5, 1.7, 2.1, and 2.5, respectively. The temperature of the fiber is 120℃ and 135℃, the crystallinity of the fiber is 70%, the grain size is 7.4nm, and the orientation degree is 0.87; during the steam drawing process, the spinning speed is 25m / min, the steam pressure is 0.6MPa, the residence time in the drawing section is 5s, and the drawing ratio is 2.5 times. After steam drawing, the crystallinity of the fiber is 79%, the grain size is 10.3nm, and the orientation degree is increased to 0.96; finally, after heat setting and winding, high-strength, high-modulus, and high-toughness polyacrylonitrile carbon fiber precursor is obtained, the linear density of the precursor is 0.63dtex, the strength and modulus are 8.5cN / dtex and 171cN / dtex respectively, and the elongation is 10.5%.

[0040] 2. In the preparation of the polyacrylonitrile carbon fiber of the present invention, the raw silk obtained in step 1 is pre-oxidized at 180-260°C, and the total pre-oxidation draft ratio is 0.96 to obtain pre-oxidized fiber; then low-temperature carbonization and high-temperature carbonization are carried out at 300-750°C and 800-1500°C, and the draft ratio is 0.97 times; thereafter, graphitization treatment is carried out at 2800°C, and finally, surface treatment, water washing, sizing, 120°C drying and wire collection are carried out to obtain high-strength, high-modulus and high-tenacity carbon fiber.

[0041] The last roller in the pre-oxidation process was counted by an online camera. The number of hair filaments in the fiber at the last outlet was 26 every 5 hours. The carbon fiber had a tensile strength of 5.8 GPa, a modulus of 389 GPa, and an elongation of 1.2%.

[0042] [Example 3]

[0043] 1. The preparation of the precursor for polyacrylonitrile carbon fiber of the present invention adopts a dry-jet wet spinning method. The intrinsic viscosity of the spinning solution used is 3.9 dL / g and the solid content is 18%. The spinning solution is accurately measured and filtered by a metering pump, and then extruded through a spinneret with 4000 holes and a pore size of 100 μm. After a 6 mm air section, it enters a coagulation bath of a dimethyl sulfoxide aqueous solution for coagulation, with a concentration of 30% and a coagulation draft ratio of 2. After that, it is washed with water and stretched in four stages with hot water at temperatures of 96°C, 97°C, 97°C, and 99°C, respectively, and the draft ratios are 1.3, 1.5, 1.8, and 2.1, respectively; after oiling, it is subjected to a two-stage drying and densification treatment at a temperature of The temperatures are 115°C and 130°C respectively, the crystallinity of the fiber is 66%, the grain size is 6.9nm, and the orientation degree is 0.8; during the steam drawing process, the spinning speed is 25m / min, the steam pressure is 0.5MPa, the residence time in the drawing section is 5s, and the drawing ratio is 2.5 times. After steam drawing, the crystallinity of the fiber is 77%, the grain size is 9.9nm, and the orientation degree is increased to 0.95; finally, after heat setting and winding, high-strength, high-modulus, and high-toughness polyacrylonitrile carbon fiber precursor is obtained, the linear density of the precursor is 0.76dtex, the strength and modulus are 9.9cN / dtex and 207cN / dtex respectively, and the elongation is 9.8%.

[0044] 2. In the preparation of the polyacrylonitrile carbon fiber of the present invention, the raw silk obtained in step 1 is pre-oxidized at 180-260°C, and the total pre-oxidation draft ratio is 0.95 to obtain pre-oxidized fiber; then low-temperature carbonization and high-temperature carbonization are carried out at 300-750°C and 800-1500°C, and the draft ratio is 0.97 times; thereafter, graphitization treatment is carried out at 2800°C, and finally, surface treatment, water washing, sizing, 120°C drying and wire collection are carried out to obtain high-strength, high-modulus and high-tenacity carbon fiber.

[0045] The last roller in the pre-oxidation process was counted by an online camera. The number of hairy fibers in the fiber at the last outlet was 23 every 5 hours. The carbon fiber had a tensile strength of 5.7 GPa, a modulus of 376 GPa, and an elongation of 1.4%.

[0046] [Example 4]

[0047] 1. The preparation of the precursor for polyacrylonitrile carbon fiber of the present invention adopts a dry-jet wet spinning method. The intrinsic viscosity of the spinning solution used is 4.2 dL / g and the solid content is 18%. The spinning solution is accurately measured and filtered by a metering pump, and then extruded through a spinneret with 4000 holes and a pore size of 100 μm. After passing through an 8 mm air section, it enters a coagulation bath of a dimethyl sulfoxide aqueous solution for coagulation, with a concentration of 30% and a coagulation draft ratio of 2.5. After that, it is washed with water and stretched in four stages with hot water at temperatures of 95°C, 96°C, 98°C, and 99°C, respectively, and the draft ratios are 1.4, 1.6, 1.8, and 2.3, respectively; after oiling, it is subjected to a two-stage drying and densification treatment, and the temperature is divided into The temperature of the steam drawing process was 120℃ and 130℃ respectively, the crystallinity of the fiber was 68%, the grain size was 7.1nm, and the orientation degree was 0.83; the spinning speed during the steam drawing process was 25m / min, the steam pressure was 0.5MPa, the residence time in the drawing section was 5s, and the drawing ratio was 2.5 times. After steam drawing, the crystallinity of the fiber was 78%, the grain size was 10.1nm, and the orientation degree was increased to 0.96; finally, after heat setting and winding, high-strength, high-modulus, and high-toughness polyacrylonitrile carbon fiber precursor was obtained, the linear density of the precursor was 0.72dtex, the strength and modulus were 10.7cN / dtex and 212cN / dtex respectively, and the elongation was 9.1%.

[0048] 2. In the preparation of the polyacrylonitrile carbon fiber of the present invention, the raw silk obtained in step 1 is pre-oxidized at 180-260°C, and the total pre-oxidation draft ratio is 0.95 to obtain pre-oxidized fiber; then low-temperature carbonization and high-temperature carbonization are carried out at 300-750°C and 800-1500°C, and the draft ratio is 0.97 times; thereafter, graphitization treatment is carried out at 2800°C, and finally, surface treatment, water washing, sizing, 120°C drying and wire collection are carried out to obtain high-strength, high-modulus and high-tenacity carbon fiber.

[0049] The last roller in the pre-oxidation process was counted by an online camera. The number of hair filaments in the fiber at the last outlet was 25 every 5 hours. The carbon fiber had a tensile strength of 5.7 GPa, a modulus of 382 GPa, and an elongation of 1.3%.

[0050] [Example 5]

[0051] 1. The preparation of the precursor for polyacrylonitrile carbon fiber of the present invention adopts a dry-jet wet spinning method. The intrinsic viscosity of the spinning solution used is 3.6 dL / g and the solid content is 18%. The spinning solution is accurately measured and filtered by a metering pump, and then extruded through a spinneret with 4000 holes and a pore size of 100 μm. After a 6 mm air section, it enters a coagulation bath of a dimethyl sulfoxide aqueous solution for coagulation, with a concentration of 30% and a coagulation draft ratio of 2. After that, it is washed with water and stretched in four stages with hot water at temperatures of 96°C, 97°C, 97°C, and 99°C, respectively, and the draft ratios are 1.3, 1.4, 1.7, and 2.1, respectively; after oiling, it is subjected to a two-stage drying and densification treatment, and the temperature is divided into The temperature of the steam drawing process was 115℃ and 125℃ respectively, the crystallinity of the fiber was 66%, the grain size was 6.7nm, and the orientation degree was 0.79; during the steam drawing process, the spinning speed was 25m / min, the steam pressure was 0.4MPa, the residence time in the drawing section was 5s, and the drawing ratio was 2.5 times. After steam drawing, the crystallinity of the fiber was 76%, the grain size was 9.8nm, and the orientation degree was increased to 0.95; finally, after heat setting and winding, high-strength, high-modulus, and high-toughness polyacrylonitrile carbon fiber precursor was obtained, the linear density of the precursor was 0.78dtex, the strength and modulus were 9.4cN / dtex and 196cN / dtex respectively, and the elongation was 10.2%.

[0052] 2. In the preparation of the polypropylene carbon fiber of the present invention, the raw silk obtained in step 1 is pre-oxidized at 180-260°C, and the total pre-oxidation draft ratio is 0.95 to obtain pre-oxidized fiber; then low-temperature carbonization and high-temperature carbonization are carried out at 300-750°C and 800-1500°C, and the draft ratio is 0.96 times; thereafter, graphitization treatment is carried out at 2800°C, and finally, surface treatment, water washing, sizing, 120°C drying and wire collection are carried out to obtain high-strength, high-modulus and high-tenacity carbon fiber.

[0053] The last roller in the pre-oxidation process was counted by an online camera. The number of hairy fibers in the fiber at the last outlet was 22 every 5 hours. The carbon fiber had a tensile strength of 5.6 GPa, a modulus of 371 GPa, and an elongation of 1.5%.

[0054] [Comparative Example 1]

[0055] 1. Preparation of precursor for polyacrylonitrile carbon fiber adopts dry-jet wet spinning method. The characteristic viscosity of the spinning solution used is 3.5dL / g and the solid content is 18%. The spinning solution is accurately measured and filtered by a metering pump, and then extruded through a spinneret with 4000 holes and a pore size of 100μm. After a 5mm air section, it enters a coagulation bath of a dimethyl sulfoxide aqueous solution for coagulation, with a concentration of 30% and a coagulation draft ratio of 2. After washing, four-stage hot water drafting is performed at temperatures of 95℃, 96℃, 97℃, and 99℃, and draft ratios of 1.3, 1.4, 1.5, and 1.7 respectively; after oiling, two-stage drying and densification treatment is performed at temperatures of 1 At 20℃ and 130℃, the crystallinity of the fiber is 65%, the grain size is 6.9nm, and the orientation degree is 0.78; during the steam drawing process, the spinning speed is 25m / min, the steam pressure is 0.3MPa, the residence time in the drawing section is 8s, and the drawing ratio is 2.5 times. After steam drawing, the crystallinity of the fiber is 76%, the grain size is 10.7nm, and the orientation degree is increased to 0.93; finally, after heat setting and winding, high-strength, high-modulus, and high-toughness polyacrylonitrile carbon fiber precursor is obtained, the linear density of the precursor is 0.88dtex, the strength and modulus are 8.7cN / dtex and 183cN / dtex respectively, and the elongation is 10.1%.

[0056] 2. Preparation of polyacrylonitrile carbon fiber. The raw silk obtained in step 1 is pre-oxidized at 180-260°C, and the total pre-oxidation draft ratio is 0.95 to obtain pre-oxidized fiber; then low-temperature carbonization and high-temperature carbonization are carried out at 300-750°C and 800-1500°C, and the draft ratio is 0.96 times; then graphitization is carried out at 2800°C, and finally surface treatment, water washing, sizing, 120°C drying and wire collection are carried out to obtain high-strength, high-modulus and high-tenacity carbon fiber.

[0057] Through the online camera to count the last roller in the pre-oxidation process, the number of hairs in the fiber at the last outlet was 43 every 5 hours, the tensile strength of the carbon fiber was 5.3 GPa, the modulus was 352 GPa, and the elongation was 1.3%.

[0058] [Comparative Example 2]

[0059] 1. Preparation of precursor for polyacrylonitrile carbon fiber adopts dry-jet wet spinning method. The intrinsic viscosity of the spinning solution used is 3.8dL / g and the solid content is 18%. The spinning solution is accurately measured and filtered by a metering pump, extruded through a spinneret with 4000 holes and a pore size of 100μm, and then enters a coagulation bath of a dimethyl sulfoxide aqueous solution for coagulation, with a concentration of 30% and a coagulation draft ratio of 3. After washing, four-stage hot water drafting is performed at temperatures of 96°C, 97°C, 98°C, and 99°C, respectively, and the draft ratios are 1.4, 1.8, 2.2, and 2.5, respectively; after oiling, two-stage drying and densification treatment is performed at temperatures of At 130℃ and 145℃, the crystallinity of the fiber is 78%, the grain size is 6.3nm, and the orientation degree is 0.61; during the steam drawing process, the spinning speed is 25m / min, the steam pressure is 0.5MPa, the residence time in the drawing section is 3s, and the drawing ratio is 3.5 times. After steam drawing, the crystallinity of the fiber is 91%, the grain size is 7.7nm, and the orientation degree is increased to 0.79; finally, after heat setting and winding, high-strength, high-modulus, and high-toughness polyacrylonitrile carbon fiber precursor is obtained, the linear density of the precursor is 0.59dtex, the strength and modulus are 7.1cN / dtex and 159cN / dtex respectively, and the elongation is 7.2%.

[0060] 2. Preparation of polyacrylonitrile carbon fiber. The raw silk obtained in step 1 is pre-oxidized at 180-260°C, and the total pre-oxidation draft ratio is 0.95 to obtain pre-oxidized fiber; then low-temperature carbonization and high-temperature carbonization are carried out at 300-750°C and 800-1500°C, and the draft ratio is 0.95 times; then graphitization is carried out at 2800°C, and finally surface treatment, water washing, sizing, 120°C drying and wire collection are carried out to obtain high-strength, high-modulus and high-tenacity carbon fiber.

[0061] The last roller in the pre-oxidation process was counted by an online camera. The number of hair filaments in the fiber at the last outlet was 51 every 5 hours. The carbon fiber had a tensile strength of 4.7 GPa, a modulus of 347 GPa, and an elongation of 0.8%.

[0062] [Comparative Example 3]

[0063] 1. Preparation of precursor for polyacrylonitrile carbon fiber adopts dry-jet wet spinning method. The intrinsic viscosity of the spinning solution used is 3.6dL / g and the solid content is 18%. The spinning solution is accurately measured and filtered by a metering pump, and then extruded through a spinneret with 4000 holes and a pore size of 100μm. After a 6mm air section, it enters a coagulation bath of a dimethyl sulfoxide aqueous solution for coagulation, with a concentration of 30% and a coagulation draft ratio of 2.5. After washing, four-stage hot water drafting is performed at temperatures of 95°C, 97°C, 98°C, and 99°C, and the draft ratios are 1.3, 1.4, 1.4, and 1.6, respectively; after oiling, two-stage drying and densification treatment is performed at temperatures of At 110℃ and 130℃, the crystallinity of the fiber is 59%, the grain size is 5.8nm, and the orientation degree is 0.76; during the steam drawing process, the spinning speed is 25m / min, the steam pressure is 0.2MPa, the residence time in the drawing section is 5s, and the drawing ratio is 1.5 times. After steam drawing, the crystallinity of the fiber is 65%, the grain size is 7.0nm, and the orientation degree is increased to 0.90; finally, after heat setting and winding, high-strength, high-modulus, and high-toughness polyacrylonitrile carbon fiber precursor is obtained, the linear density of the precursor is 1.00dtex, the strength and modulus are 7.6cN / dtex and 169cN / dtex respectively, and the elongation is 11.8%.

[0064] 2. Preparation of polyacrylonitrile carbon fiber. The raw silk obtained in step 1 is pre-oxidized at 180-260°C, and the total pre-oxidation draft ratio is 0.95 to obtain pre-oxidized fiber; then low-temperature carbonization and high-temperature carbonization are carried out at 300-750°C and 800-1500°C, and the draft ratio is 0.96 times; then graphitization is carried out at 2800°C, and finally surface treatment, water washing, sizing, 120°C drying and wire collection are carried out to obtain high-strength, high-modulus and high-tenacity carbon fiber.

[0065] Through the online camera to count the last roller in the pre-oxidation process, the number of hair fibers in the fiber at the last outlet was 31 every 5 hours, the carbon fiber tensile strength was 4.3 GPa, the modulus was 331 GPa, and the elongation was 2.4%.

[0066] [Comparative Example 4]

[0067] 1. Preparation of precursor for polyacrylonitrile carbon fiber adopts dry-jet wet spinning method. The intrinsic viscosity of the spinning solution used is 3.7dL / g and the solid content is 18%. The spinning solution is accurately measured and filtered by a metering pump, and then extruded through a spinneret with 4000 holes and a pore size of 100μm. After a 6mm air section, it enters a coagulation bath of a dimethyl sulfoxide aqueous solution for coagulation, with a concentration of 30% and a coagulation draft ratio of 2. After washing, four-stage hot water drafting is performed at temperatures of 95℃, 96℃, 97℃, and 99℃, and the draft ratios are 1.3, 1.4, 1.4, and 1.5 respectively; after oiling, two-stage drying and densification treatment is performed at temperatures of 1 At 15℃ and 125℃, the crystallinity of the fiber is 52%, the grain size is 5.1nm, and the orientation degree is 0.57; during the steam drawing process, the spinning speed is 25m / min, the steam pressure is 0.3MPa, the residence time in the drawing section is 5s, and the drawing ratio is 2.5 times. After steam drawing, the crystallinity of the fiber is 61%, the grain size is 7.3nm, and the orientation degree is increased to 0.85; finally, after heat setting and winding, high-strength, high-modulus, and high-toughness polyacrylonitrile carbon fiber precursor is obtained, the linear density of the precursor is 1.07dtex, the strength and modulus are 7.2cN / dtex and 160cN / dtex respectively, and the elongation is 12.5%.

[0068] 2. Preparation of polyacrylonitrile carbon fiber. The raw silk obtained in step 1 is pre-oxidized at 180-260°C, and the total pre-oxidation draft ratio is 0.95 to obtain pre-oxidized fiber; then low-temperature carbonization and high-temperature carbonization are carried out at 300-750°C and 800-1500°C, and the draft ratio is 0.96 times; then graphitization is carried out at 2800°C, and finally surface treatment, water washing, sizing, 120°C drying and wire collection are carried out to obtain high-strength, high-modulus and high-tenacity carbon fiber.

[0069] The last roller in the pre-oxidation process was counted by an online camera. The number of hair filaments in the fiber at the last outlet was 22 every 5 hours. The carbon fiber had a tensile strength of 4.6 GPa, a modulus of 340 GPa, and an elongation of 2.0%.

Claims

1. A method for preparing carbon fiber precursor, comprising a steam drawing step, wherein: The crystallinity of the fiber before steam drawing is 60-75%, and the orientation degree is 0.65-0.

9. After steam drawing with a steam pressure of 0.2-0.7 MPa, a drawing dwell time of 2-6 seconds, and a drawing multiple of 2-5 times, the crystallinity of the fiber is 68-90%, and the orientation degree is 0.9-0.99; the grain size of the fiber before steam drawing is 6-8 nm, and the grain size of the fiber after steam drawing is 8-10.5 nm.

2. The preparation method according to claim 1, characterized in that: The fiber has a crystallinity of 65-75% and an orientation of 0.75-0.90 before steam drawing, and has a crystallinity of 75-85% and an orientation of 0.93-0.99 after steam drawing at a steam pressure of 0.3-0.6 MPa, a drawing dwell time of 4-5 seconds, and a drawing multiple of 2-2.5 times.

3. The preparation method according to claim 1, characterized in that: The grain size of the fiber before steam drawing is 6.5-7.5 nm, and the grain size of the fiber after steam drawing is 9-10.5 nm; and / or, The strength of the steam-drawn fiber is 7-15 cN / dtex, the modulus is 150-235 cN / tex, and the elongation is 7-12%; and / or, The fiber fineness after steam drawing is 0.55-1.10 dtex.

4. The preparation method according to claim 3, characterized in that: The strength of the steam-drawn fiber is 8.5-13 cN / dtex, the modulus is 170-225 cN / tex, and the elongation is 8.5-12%; and / or, The fiber fineness after steam drawing is 0.60-0.92 dtex.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation method specifically comprises the steps of extruding polyacrylonitrile stock solution by dry-jet wet spinning, and then stretching by air segment, solidifying, washing, hot water drawing, oiling, drying and densification, steam drawing, and steam heat setting to obtain the carbon fiber precursor.

6. The preparation method according to claim 5, characterized in that: The intrinsic viscosity of the polyacrylonitrile stock solution is 3.0 to 5.5 dL / g.

7. The preparation method according to claim 6, characterized in that: The intrinsic viscosity of the polyacrylonitrile stock solution is 3.5-4.8 dL / g.

8. The preparation method according to claim 5, characterized in that: The length of the air segment is 1 to 15 mm.

9. The preparation method according to claim 8, characterized in that: The length of the air section is 5 to 10 mm.

10. The preparation method according to claim 5, characterized in that: The draft ratio of the solidification molding is 1-5.

11. The preparation method according to claim 10, characterized in that: The draft ratio of the solidification molding is 1-3.

12. The preparation method according to claim 5, characterized in that: The hot water drawing is at least level 4.

13. The preparation method according to claim 12, characterized in that: The hot water drawing temperature is 90-100° C., the total drawing ratio is greater than or equal to 4 times, and the fourth hot water drawing ratio is greater than 1.5 times.

14. The preparation method according to claim 13, characterized in that: The hot water drawing temperature is 95-99° C., the total drawing ratio is 4.5-6.0 times, and the fourth hot water drawing ratio is 1.6-3.0 times.

15. The preparation method according to claim 5, characterized in that: The drying and densification temperature is 90-160° C., and no stretching is applied.

16. The preparation method according to claim 15, characterized in that: The drying and densification temperature is 100-140°C.

17. A polyacrylonitrile carbon fiber precursor prepared by the preparation method according to any one of claims 1 to 16.

18. A high-strength, high-modulus and high-tenacity carbon fiber prepared from the polyacrylonitrile carbon fiber precursor according to claim 17.

Citation Information

Patent Citations

  • Manufacturing method of high performance wet spun polyacrylonitrile carbon fiber precursor

    CN111088543A

  • Fiber bundle of carbon fiber precursor and method for producing the same

    JP2008214795A

  • Method for producing carbon fiber precursor yarn

    JP4983641B2

  • Carbon fiber precursor fiber bundle and method for producing the same

    JP5012089B2

  • Carbon fiber precursor fiber and method of manufacturing the same

    JP2012193468A